Hierarchical Facility Location with distance constraints: Analysing the problem on a line - Pareja, Andrea (2013)
Facility Location decisions are considered as strategic decisions for many organisations, mainly because of the high-costs involved in building and implementing them. However, they are complex problems to solve because of the different variables to be considered, this is why many studies have been conducted on this area and many generic models for solving them can be found in the literature. Additionally, nowadays many organisations see the necessity to offer services as an addition to their end products; this is specially the case for manufacturing corporations in industries such as the Automotive, Aerospatiale and Technology. Thus, they have to build up a new system of facilities which can efficiently provide a set of different service levels, and as it can be expected, this increases the complexity of the original facility location problem. Therefore, the present research aims at analysing the facility location problem within a hierarchical system and simplifying it by placing the facilities on a line. The problem is first analysed in a bounded region for which a cost analysis of inventory and routing cost is made. This part of the research leads to the conclusions that it is possible to obtain certain location patterns that include the trade-off between inventory and routing costs. Later on the analysis is done within an unbounded region, in this section other location patterns are found which allow understanding the relation between the different service levels, and how it has to be considered when defining the maximum travel distances for each of them. Finally, a heuristic method is defined for placing the location patterns obtained from the analysis on an unbounded region.